The Influence of System Quality, Information Quality and Service Quality on E-Learning User Satisfaction at UIN Walisongo Semarang - Ulyanti; Syaiful Bakhri; Salsabilla, Imelia Sahda (LPPM Telkom University Surabaya, 2026)
State Islamic University (UIN) Walisongo Semarang uses the e-learning system as an online learning support, but students still face obstacles such as system errors, slow access, and data that is not updated. This study aims to analyze the influence of system quality, information quality, and service quality on user satisfaction using the DeLone and McLean models. The quantitative method was used through the distribution of questionnaires to 97 students of the 2020 cohort, and the data were analyzed using SmartPLS 3. The results showed that the quality of the system had no significant effect (t = 0.658; p > 0.05), the quality of service was also insignificant (t = 1.539; p > 0.05), while the quality of information had a significant effect on user satisfaction (t = 2.853; p < 0.05). This research contributes to the understanding of the factors that determine the success of e-learning, as well as provides practical implications in the form of the need to improve system stability, improve information features, and strengthen technical services to improve the student learning experience.